PENGARUH MODEL PEMBELAJARAN MODIFIKASI PERMAINAN TERHADAP KEBUGARAN JASMANI PADA PESERTA DIDIK PUTRA KELAS VII SMPN 3 KOTO BARU - Susanti, Desi Tri; Saputra, Deddy Rahmat; Prahagia, Yelvia (Jurnal Muara Olahraga, 2023)
ABSTRACT Based on the results of observations that researchers found in the field, the low physical fitness of VII grade male students is evident from the facts that researchers found in the process of physical fitness learning for the 1st semester of 2021/2022 school year. Only 13 students who have good physical fitness level out of 37 students, here the percentage can only be 35.14%, while 64.86% have low physical fitness levels (Physical Educater for Junior Haig School 1 Tiumang, Dharmasraya Regency). This study aims to uncover the differences in the learning model of game modification and traditional games on physical fitness of male students of class VII Male Students of Junior High School 3 Koto Baru Dharmasraya Regency) This type of research is quasi-experimental, which was conducted on Agust 1 to Ocober 2 in male students of class VII Junior High School 3 Koto Baru Dharmasraya District, amounting to 30 people. Sampling in this study using proportional random sampling techniques to obtain a sample of 24 people. The test instrument used in this study is the Indonesian Physical Fitness Test for children aged 13-15 years while the statistical data analysis technique uses the normality test, and the t-test. Based on the results of data analysis using t-test analysis. The first hypothesis is obtained tcount (10.78)> ttable (1.796) which means that there is a significant exercise effect of the learning model of game modification on physical fitness.. Keywords: Physical Fitness of Students, Game Modifications.